2018
DOI: 10.1136/bmjopen-2017-017581
|View full text |Cite
|
Sign up to set email alerts
|

Targeting skeletal muscle tissue oxygenation (StO2) in adults with severe sepsis and septic shock: a randomised controlled trial (OTO-StS Study)

Abstract: ObjectiveEvaluation of the ratio of oxyhaemoglobin to total haemoglobin in skeletal muscle (StO2) using near-infrared spectroscopy may aid in the monitoring of patients with sepsis. This study assessed the benefits and risks of targeting StO2 in adults with severe sepsis or septic shock.DesignA European randomised controlled trial was performed on two parallel groups.SettingFive intensive care units (ICU) in France, Greece, Spain and Germany were used for the study.ParticipantsA total of 103 adults with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Indeed, in this study higher severity of organ failure measured by SOFA score was associated with lower skin oxygen saturation values. Similar to our study, low thenar muscle oxygen saturation measured by near-infrared spectroscopy (NIRS) was found to be present in 60% of patients with sepsis [21], but only dynamic changes in tissue oxygenation after vascular occlusion test have been shown to be related to organ failure [22]. In our study, we targeted measurement only to the most hypoxic areas of the skin, and our data support a more direct link between hypoxia in microcirculatory beds and development of multiple organ failure.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, in this study higher severity of organ failure measured by SOFA score was associated with lower skin oxygen saturation values. Similar to our study, low thenar muscle oxygen saturation measured by near-infrared spectroscopy (NIRS) was found to be present in 60% of patients with sepsis [21], but only dynamic changes in tissue oxygenation after vascular occlusion test have been shown to be related to organ failure [22]. In our study, we targeted measurement only to the most hypoxic areas of the skin, and our data support a more direct link between hypoxia in microcirculatory beds and development of multiple organ failure.…”
Section: Discussionsupporting
confidence: 82%
“…Overall, randomized controlled trials on NIRS monitoring in critically ill adult patients are scarce. Only 2 randomized controlled trials of NIRS-guided treatment were identified by our searches: a small pilot study 37 and the subsequent larger trial 38 by the same study group. However, these studies could not be included in the review, as they also included patients with severe sepsis.…”
Section: Review Question 1: Does Nirs Monitoring Improve Patient-centmentioning
confidence: 99%
“…However, the utility of NIRS in the management of critically ill patients is still a matter of debate. A recent randomized trial study of StO 2 -guided resuscitation with sepsis or septic shock patients at ICU admission found that the inclusion of StO 2 > 80% as a target in the algorithm for early goal-directed therapy did not improve clinical outcomes [42]. Moreover, this experimental algorithm of resuscitation was associated with more time on mechanical ventilation, more blood transfusion and more use of inotropes [42].…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized trial study of StO 2 -guided resuscitation with sepsis or septic shock patients at ICU admission found that the inclusion of StO 2 > 80% as a target in the algorithm for early goal-directed therapy did not improve clinical outcomes [42]. Moreover, this experimental algorithm of resuscitation was associated with more time on mechanical ventilation, more blood transfusion and more use of inotropes [42]. However, another randomized controlled pilot study was performed comparing a peripheral perfusion-guided early fluid resuscitation with a classical strategy based on MAP, CVP and CI in septic shock patients admitted to the ICU [43].…”
Section: Discussionmentioning
confidence: 99%